Total glenoid fractures - Bartonicek, J; Tucek, M; Klika, D; Obruba, P (Rozhledy v chirurgii, 2016)
INTRODUCTION: Fractures affecting the entire glenoid fossa are termed comminuted or total glenoid fractures. However, there are no detailed studies of total glenoid fractures, and only brief mentions can be found in the literature. METHODS: The group comprised 12 patients (mean age, 39 years), who sustained 13 fractures of the glenoid fossa. In all the fractures, all parts of the glenoid fossa were separated from the scapular neck or body. In total 5 patients (6 fractures) were treated non-operatively and 7 patients were operated on. The method of treatment was based on displacement of the fragments, the patient´s general and local conditions. Indication for operative treatment was displacement of articular fragments of more than 3mm. This criterion was met by 10 patients (11 fractures). Owing to the general or local condition, operation was contraindicated in 2 patients with 3 fractures; one patient refused the operation. One patient with a bilateral fracture was lost to follow-up. RESULTS: According to the site of separation of articular fragments, the fractures were divided into three groups - the separation line passed through the anatomical neck; through the coracoid process or surgical neck of the scapula; or through the scapular body. In 6 of the 7 operated patients, a good or very good result was achieved. In 2 patients with minimal fragment dislocation treated non-operatively, the fractures healed in an anatomical position and full range of motion was achieved. In 2 patients with severe fragment displacement treated non-operatively, the healing resulted in glenoid fossa incongruence and painful and limited range of motion. CONCLUSION: Fractures of the entire glenoid fossa are the most severe injuries to scapula. Their diagnosis requires CT examination, including 3D CT reconstruction with subtraction of the surrounding bones. Displaced fractures are indicated for operative treatment from the Judet approach.Key words: scapular fractures glenoid fractures classification, operative treatment Judet approach.
Keywords: pasivní pohybová terapie CPM; Male; Immobilization; Fracture Healing; imobilizace; Adolescent; Fracture Fixation; Adult; Aged; dospělí; mužské pohlaví; senioři; Motion Therapy, Continuous Passive; fraktury proximálního humeru; mladiství; Shoulder Fractures; lidé; ženské pohlaví; Humans; Female; lidé středního věku; hojení fraktur; fixace fraktury; Middle Aged